Inventura knjižničnega gradiva - Abe, Marijana (Knjižnica, 2014)
The article shows the importance of collection inventory in a library. The reasons for conducting an inventory, the review of methods and types of an inventory are given. Instructions for conducting an inventory with special emphasis on the RFID technology are described. A lot has been written about RFID so far but there is only a small number of empirical studies of the evaluation of RFID and barcode technology. The number of articles dealing with RFID technology, from the early 1990s to 2005, increased from almost none to almost 9,000. Some published studies on automated inventory of library collection are presented.
Keywords: knjižnice; library; inventory; inventura; RFID technology; tehnologija RFID; barcode technology; črtne kode